Políticas públicas educacionais e fluxos migratórios : entre os desafios climáticos e as poéticas da educação ambiental - Simione, Roberta Moraes (2021)
The phenomenon of migration is not recent in the history of humanity, however, nowadays it has acquired different shapes and causes. Scholars warn that in the coming years the migration flows will gradually intensify mainly as a result of environmental disasters from climate collapse. Faced this dramatic scenario, several peoples will be expelled from their territories and new shelters will be sought. In this circumscribed context in the Capitalocene era, whose pillars support denial theories which make it impossible to know the causes and consequences of climate change, many social groups will suffer as a result of environmental and climate injustices. Migrants correspond to one of these groups, since many of them are in a vulnerable situation as well as being victims of social violence. In this thesis, I seek to interpret the documents constructed in the Forum on Migration Flows and the narratives of those who migrated, act and acted in the promotion of public policies for migrants in the State of Mato Grosso; people who, in a certain way, follow or know the work developed by the Pastoral Care Center for migrants; participated in the Forum on Migration Flows; and fight and long for the existence of educational public policies for migrants, in order to discuss the State’s role in promoting educational public policies for migrants in the light of Environmental Education for migrants and Climate Justice. With a phenomenological nature, the chosen methodology was the Cartography of the Imaginary, which made it possible to interpret the interviewees’ documents and narratives, relating to the four Bachelardian archetypes: Water, Earth, Fire and Air. Based on the images that compose these archetypes, I created migration images exercising the duty and right of researcher. In relation to the results, the situation of vulnerability in which many migrants find themselves reveals the omission of the State in attending this group in a dignified and efficient way. In this context, it is evident how necessary partnerships are between social movements aiming at promoting inclusive public policies for the migrants in the State and, thus, defending the need for educational public policies based on ethics and human rights.